Current Advances in the Use of Mushrooms as Therapeutics for Lung Cancer: A Review - Edward Thato Khunoana; Sanah Malomile Nkadimeng (Molecules)
Medicinal mushrooms have become increasingly important in the pharmaceutical industry because they contain a wealth of bioactive compounds and offer various nutritional benefits. These qualities also contribute to their widespread use in cooking. Global mycologists have suggested that a deeper understanding of mushrooms can aid in treating a variety of cancers at different stages. The excellent anticancer potential of fungi has inevitably attracted the attention of researchers, given the ever-increasing number of cases of lung cancer. Thus, the purpose of this review was to compile and synthesize the existing scientific literature about the potential of mushroom extracts particularly towards lung cancer prevention. A comprehensive literature search was conducted in electronic databases to identify relevant studies for the review. We found that 26 distinct kinds of mushrooms, prepared in over 10 different solvents, were used to make extracts that decreased the viability of different types of lung cancer cells (A549, NCI-H460, 3LL, H1264 cells etc.). We also examined a range of experimental models, including cell cultures (in vitro), mouse models (in vivo), as well as case studies and randomized controlled trials. The investigated mushrooms’ effective mechanisms included: a reduction in the growth of cancer cells; an imbalanced percentage of cells in different phases of the cell cycle; an increase in autophagy and phagocytosis; an enhanced immune response; and the induction of cell apoptosis through the upregulation of pro-apoptotic factors and the downregulation of anti-apoptotic genes. Considering that mushrooms are consumed as a daily supplement, their potent pro-apoptotic properties and high antiproliferative efficacy are advantageous and could provide a model for further studies in this field as well as novel drug therapies and cancer treatments.